1981
DOI: 10.3109/00016348109158126
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Red Blood Cell Folate During Normal Pregnancies

Abstract: Plasma and red cell folate concentrations (Lactobacillus casei activity) have been studied in 43 women during pregnancy. Iron, but no folic acid supplement was given. The plasma folate concentrations decreased significantly during pregnancy and were lower than in the reference cases at term. The red cell folate concentrations were compatible with the reference material during early pregnancy, and significantly higher than the reference material at term. A significant decrease was observed during the last two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 22 publications
5
19
0
Order By: Relevance
“…The fact that the levels of red blood cell folates in the intervillous space of the placenta were, on the average, almost identical to those in the mother and the fact that the correlation coefficient between them was close to one indicate that the erythrocytes suffer no alterations in terms of their folate stores when circulating in the intervillous space of the placenta. Positive correlation has been reported between serum and red blood cell folate concentrations [2,3,5,7] and the results obtained in the present paper confirm these observations. Thus, the correlation existing between the red blood cell folate levels in mothers and newborns may simply be the consequence of the correlation between serum folate levels in the mother-newborn binomium.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The fact that the levels of red blood cell folates in the intervillous space of the placenta were, on the average, almost identical to those in the mother and the fact that the correlation coefficient between them was close to one indicate that the erythrocytes suffer no alterations in terms of their folate stores when circulating in the intervillous space of the placenta. Positive correlation has been reported between serum and red blood cell folate concentrations [2,3,5,7] and the results obtained in the present paper confirm these observations. Thus, the correlation existing between the red blood cell folate levels in mothers and newborns may simply be the consequence of the correlation between serum folate levels in the mother-newborn binomium.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have shown that serum and red blood cell folate levels in full-term newborns are higher than in their mothers [2,5,10,14], and these observations were confirmed in the present investigation. This fact suggests the presence of a mechanism that guarantees adequate amounts of this vitamin to the fetus.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Efficacy of FA administration A relation between maternal folate status and reproductive performance is reported to exist in several species including humans (4,15,19), rats (21), guinea pigs (7), and pigs (6, 9,10,12,20,22,23). It has been considered that folate requirement increases during pregnancy (8).…”
Section: Plasma Active Folatesmentioning
confidence: 99%
“…This hypothesis suggests a possible relation between the folate status in the mother and fetal growth. Indeed, the effects of folate on increases in birthweight have been observed with some consistency among poorly nourished women [7,8].…”
Section: Introductionmentioning
confidence: 99%